La controverse sur l’archiprêtre, ou les catholiques élisabéthains dans les coulisses de la clandestinité - Sandra Jusdado-Mollmann (Revue LISA)
The most divided communities ordinarily choose to unite in the face of a powerful enemy. But when a community is ordered by the same religious ideology, when it has been forced into clandestinity, and when its very survival is at stake, this strategy seems all the more appropriate. Such is the logic that should have determined the choices of Elizabethan Catholics. But strangely enough, they did not opt for this strategy. The aim of this article is to analyse the fracture that divided the clandestine Roman Catholic clergy during the reign of Elizabeth I and which came out in the open under the name of “the archpriest controversy”. We will analyse the causes, the unfolding and the outcome of this internal scission. We will demonstrate that, contrary to what might have been expected, not only was this controversy — and the divisions it provoked within the persecuted community — the very element that ensured the survival of Catholicism in England, but it also brought about the advent of a specifically English form of Catholicism.